2023
DOI: 10.7554/elife.84679
|View full text |Cite
|
Sign up to set email alerts
|

Comparative single-cell profiling reveals distinct cardiac resident macrophages essential for zebrafish heart regeneration

Abstract: Zebrafish exhibit a robust ability to regenerate their hearts following injury, and the immune system plays a key role in this process. We previously showed that delaying macrophage recruitment by clodronate liposome (-1d_CL, macrophage-delayed model) impairs neutrophil resolution and heart regeneration, even when the infiltrating macrophage number was restored within the first-week post injury (Lai et al., 2017). It is thus intriguing to learn the regenerative macrophage property by comparing these late macro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…Adult zebrafish are known to have populations of cTMs in the steady state and cardiac MNP populations expand following cardiac injury 24,29,62 . A recent study has highlighted the heterogeneity of resident cTMs and their involvement in promoting regeneration 42 echoing what has been described in neonatal mice 63 . However, we are yet to fully understand the spatial distribution of these cells in the heart, the roles played by distinct MNP lineages and to confirm strategies to identify these subpopulations.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Adult zebrafish are known to have populations of cTMs in the steady state and cardiac MNP populations expand following cardiac injury 24,29,62 . A recent study has highlighted the heterogeneity of resident cTMs and their involvement in promoting regeneration 42 echoing what has been described in neonatal mice 63 . However, we are yet to fully understand the spatial distribution of these cells in the heart, the roles played by distinct MNP lineages and to confirm strategies to identify these subpopulations.…”
Section: Resultsmentioning
confidence: 71%
“…Multiple studies have provided important insight into the ontogeny and maintenance of microglia 65,67,70,79 , but much of this hasn't been investigated in other tissues. Recent studies using single cell sequencing (scRNA-seq) are advancing our understanding of immune cell heterogeneity in the zebrafish heart and other organs [41][42][43]66,70 but much of this has been derived from mpeg1.1 expressing cells and is yet to be translated into new tools to define the distribution of these subpopulations. Our data indicates that using csf1ra and mpeg1.1 transgenic lines it is possible to identify four separate immune cell populations in the homeostatic heart and we have shown that these cells have distinct morphology, distribution, and behaviour in cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we examined the spatial correlation of ptx3a + cells with macrophages in the hearts of injured mpeg:EGFP;ptx3a:mCherry fish and found many EGFP + cells associated with mCherry + signals ( Figure 3B ). As different macrophage subtypes exist in the wound, 12 , 37 , 51 we then assessed macrophage type with known markers: tnfα for pro-inflammatory macrophages 52 and mrc1b 53 and cxcr4b 54 , 55 for reparative macrophages ( Figures 3C , 3D , S1F , and S1G ). We also quantified the spatial correlation of macrophages and ptx3a + cells by the distance of these cells in three situations: (1) macrophages surrounded by ptx3a + cells, (2) macrophages within 1 μm of ptx3a + cells, excluding situation 1, and (3) macrophages more than 1 μm away from ptx3a + cells.…”
Section: Resultsmentioning
confidence: 99%
“…This regenerative ability of cardiac muscle cells can be achieved by dedifferentiation and proliferation of pre-existing CMs [7][8][9] . The regenerative events in CMs are orchestrated by molecular signals provided by activated non-muscular cells, including epicardium, endocardium, and immune cells, which create a regenerative niche 7,[10][11][12][13][14][15] . Furthermore, similar to injured mammalian hearts, zebrafish exhibit an acute response to cardiac injury by forming fibrotic tissue at the injury site 16 .…”
Section: Introductionmentioning
confidence: 99%